Regulation of Nutrient Transporters by Metabolic and Environmental Stresses - Babst, Markus (Curr Opin Cell Biol, 2020)
The yeast plasma membrane is a selective barrier between an erratic environment and the cell’s metabolism. Nutrient transporters are the gatekeepers that control the import of molecules feeding into the metabolic pathways. Nutrient import adjusts rapidly to changes in metabolism and the environment, which is accomplished by regulating the surface expression of transporters. Recent studies indicate that the lipid environment in which transporters function regulates ubiquitination efficiency and endocytosis of these proteins. Changes in the lipid environment are caused by lateral movements of the transporters between different membrane domains and by the influence of the extracellular environment on the fluidity of the plasma membrane.